METODE DAKWAH TERAPEUTIK - Nazirman Nazirman (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2018)
Therapeutic Da'wah is an activity to invite, call upon, and motivate people to maintain and maintain a healthy quality of life and life through the application of Islamic values in life. Healthy becomes one of the most important aspects in creating a happy life in the world and the hereafter. To realize this condition the missionary activity refers to apostolic vision and mission based on the Qur'anic verse al-Baqarah verse 151, so the method used is the recitation method, tazkiyah and taklimah. Whereas in the Tha-Haa verse 2, al-Waqi`ah verse 73, al-Haqqah verse 12, al-Munzammil verse 19, al-Mudatsir verse 54 and al-Insan verse 29 and Abasa verse 11 using tazkirah. Recitations are interpreted as reading strategic, tazkiyah is interpreted as purified, the meaning is interpreted by the learning method, and tazkirah is expotulation. The four methods are also a special technique in the bi-l-Irasyad da'wah derived from the method of da'wah bi al-mauizhah al-hasanah.